Angular measurement errors in underground mine surveying reference networks - Nazarenko, V. O.; Brui, H. V.; Krivoruchko, А. O.; Levytskyi, V. H.; Назаренко , В. О.; Бруй, Г. В.; Криворучко, А. О.; Левицький, В. Г. (Державний університет "Житомирська політехніка", 2024)
Surveyorʼs reference networks are the main geometric basis of all underground surveys and consist of polygonometric courses laid, as a rule, along capital and main mine workings. When laying polygons along mine workings, horizontal angles between each two adjacent sides of the course, inclination angles and lengths of the course sides are measured. Each measurement is performed with some error, which eventually leads to errors in determining the coordinates of polygon points. The peculiarities of underground polygonometric courses due to their forced configuration determined by mine workings, the presence of forced short sides and a limited number of starting points, contribute to the rapid accumulation of errors in the course as the distance from the starting points. The accuracy of measurements in the polygonometric passes, laid in the construction of underground reference networks, is characterized by the general normative indicators: the mean square error of measurement of horizontal angles of 20", vertical angles – 30". According to the requirements of the current normative instructions, the measurement of angles in underground polygonometric passages should be made with theodolites of T15 type or theodolites with the accuracy of the reference device not less than 15". The last requirement applies to theodolites of T30 type. In polygonometric moves laid along the mine workings with an angle of inclination of less than 30 °, the angles are measured in one repetition or reception. Measurement of angles in mine workings with an inclination angle of more than 30 ° is recommended to perform a method of techniques (at least two), observing the following rule: before each technique set the vertical axis of rotation of the theodolite in a plumb position and re-centering the device. If we proceed only from the instrumental component of the total error of angle measurement to ensure the mean square error of horizontal angle measurement ±20" theodolite type T15 should perform angle measurement in one full method, and theodolite T30 – in three methods. Instrumental error of angle measurement is caused by errors of sighting, counting, eccentricity of the limb and alidade, incorrect geometry of the horizontal circle, non-verticality of the theodolite rotation axis. The studies of errors in measuring horizontal angles in underground surveyorʼs polygonometric courses made it possible to draw the following conclusions: – the recommendations of the instruction «Surveying work at coal mines and surface mines» on the use of theodolites with a readout accuracy of 15" does not provide the required accuracy of horizontal angle measurements; – when using theodolites of T15 type to measure the angle with sides up to 20 m it is necessary to use only automatic centering of theodolite and signals; The scientific paper contains charts for determining the ways of centering and the number of methods of measuring horizontal angles in underground surveyorʼs polygonometric moves. Маркшейдерські опорні мережі є головною геометричною основою всіх підземних зйомок і складаються з полігонометричних ходів, що прокладаються, як правило, капітальними та основними гірничими виробками. Під час прокладання полігонів по виробках вимірюють горизонтальні кути між кожними двома суміжними сторонами ходу, кути нахилу і довжини сторін ходу. Кожне вимірювання виконується з якоюсь похибкою, що в підсумку призводить до помилок визначення координат пунктів полігонів. Особливості підземних полігонометричних ходів зумовлені їхньою вимушеною конфігурацією, яку визначають гірничі виробки, наявністю вимушено коротких сторін і обмеженим числом вихідних пунктів, сприяють швидкому накопиченню помилок у ходах у міру віддалення від вихідних пунктів. Точність вимірювань у полігонометричних ходах, що прокладаються під час побудови підземних опорних мереж, характеризується загальними нормативними показниками: середня квадратична похибка вимірювання горизонтальних кутів – 20", вертикальних кутів – 30". Згідно з вимогами чинних нормативних інструкцій вимірювання кутів у підземних полігонометричних ходах має проводитися теодолітами типу Т15 або теодолітами з точністю відлікового пристосування не менше 15". Остання вимога стосується теодолітів типу Т30. У полігонометричних ходах, що прокладаються виробками з кутом нахилу менше 30°, кути вимірюють одним повторенням або прийомом. Вимірювання кутів у виробках із кутом нахилу понад 30° рекомендується виконувати способом прийомів (не менше ніж два), дотримуючись такого правила: перед кожним прийомом встановлюють вертикальну вісь обертання теодоліта у прямовисне положення і повторно центрують прилад. Якщо виходити тільки з інструментальної складової загальної похибки вимірювання кута для забезпечення середньої квадратичної похибки вимірювання горизонтального кута ±20" теодолітом типу Т15 необхідно виконати вимірювання кута одним повним прийомом, а теодолітом Т30 – трьома прийомами. Інструментальна похибка вимірювання кута зумовлена помилками візування, відлічування, ексцентриситету лімба й алідади, рену, неправильної геометрії горизонтального кола, невертикальністю осі обертання теодоліта. Виконані в роботі дослідження похибок вимірювання горизонтальних кутів у підземних маркшейдерських полігонометричних ходах дозволили зробити такі висновки: – рекомендації діючої інструкції з використання теодолітів з точністю відліковування 15" не забезпечує необхідну точність вимірювань горизонтального кута; – у разі використання теодолітів типу Т15 для вимірювання кута зі сторонами до 20 м варто застосовувати винятково автоматичне центрування теодоліта і сигналів. У науковій роботі наводяться графіки для визначення способів центрування та кількості прийомів вимірювання горизонтальних кутів у підземних маркшейдерських полігонометричних ходах.
Похибки кутових вимірювань у підземних маркшейдерських опорних мережах
Keywords: підземні маркшейдерські полігонометричні ходи; точність вимірювання горизонтальних кутів; спосіб центрування; кількість прийомів; underground surveyorʼs polygonometric passages; accuracy of horizontal angles measurement; centering method; number of techniques